Breeding indoor watercress for enhanced crop biofortification: harnessing natural variation of wild germplasm - Qian, Yufei; Katz, Ella; Kliebenstein, Daniel J.; Taylor, Gail (Frontiers in Plant Science, 2025)
We quantified the natural genetic variation of a diverse collection of wild watercress germplasm, consisting of 32 accessions collected from 16 locations in nine countries worldwide and grown in a controlled indoor environment with contrasting blue light regimes. Significant phenotypic diversity was identified for all three categories of traits: morphology and yield varied by 68% across the population (leaf size, biomass production, and stem length), with sensory (sugar content and brix), and nutritional quality (glucosinolates, vitamin C, carotenoids) varying by 45% and 43% respectively. Using two LED light regimes, control and additional blue light exposure, revealed that the watercress nutritional profile is plastic, and that the magnitude and direction of plastic responses vary depending on genotype and trait. Two glucosinolate compounds responded differently to blue light, as indolyl-3-methyl-glucosinolate increased while 4-phenylbutyl-glucosinolate decreased, but the other glucosinolate compounds tested, namely, 6-methyl-sulfinyloctyl-glucosinolate, 7-methyl-sulfinyloctyl-glucosinolate, 8-methyl-sulfinyloctyl-glucosinolate, and 2-phenylethyl-glucosinolate, showed varying responses to blue light depending on genotype. Carotenoids, especially lutein, increased consistently across the population under the additional blue light treatment, while vitamin C, glucose, and antioxidant capacity (Ferric reducing antioxidant power of plasma) all decreased after the blue light treatment. Plants were smaller and had lower biomass, but developed more leaves and branches under additional blue light. Using this phenotypic information, we identified donor germplasm lines and proposed a breeding scheme for improved nutrition and flavor alongside enhanced yield in indoor, controlled environments where there is a paucity of data. Six elite genotypes were selected that will produce a new progeny population of favorable characteristics in this powerhouse leafy-green crop.